Basal Cell Carcinoma : Evaluation Of Clinical And Histologic Variables - Mahanthesh Mamata; Rameshkumar Karuna (Wolters Kluwer Medknow Publications, 2004)
A retrospective review of 32 patients with basal cell carcinoma was performed with aims to characterize the demographic profile and to analyze the clinical and histological parameters influencing the treatment of basal cell carcinoma. The maximum number occurred in the sixth decade with an unusual female preponderance. Hisologically, the classic type predominated while the other types included pigmented, morphoea, metatypical, adenoid, eccrine, firoepihelioma and superficial spreading type. All patients had excision of the tumour with involvement of surgical margin in three of them. None of the three patients belonged to aggressive histological types, such as morphoea or metatypical type. Two year follow-up showed no recurrence. Size of the tumor less than 2 cm, absence of ulceration and a good inflammatory response were probably other reasons for non-recurrence.